Programmed death of intestinal epithelial cells in neonatal necrotizing enterocolitis: a mini-review - Yang, Shuo; Wei, Xin; Zhong, Yuting; Guo, Conglu; Liu, Xinzhu; Wang, Zhibin; Tu, Ye (Frontiers in Pediatrics, 2023)
Necrotizing enterocolitis (NEC) is one of the most fatal diseases in premature infants. Damage to the intestinal epithelial barrier (IEB) is an important event in the development of intestinal inflammation and the evolution of NEC. The intestinal epithelial monolayer formed by the tight arrangement of intestinal epithelial cells (IECs) constitutes the functional IEB between the organism and the extra-intestinal environment. Programmed death and regenerative repair of IECs are important physiological processes to maintain the integrity of IEB function in response to microbial invasion. However, excessive programmed death of IECs leads to increased intestinal permeability and IEB dysfunction. Therefore, one of the most fundamental questions in the field of NEC research is to reveal the pathological death process of IECs, which is essential to clarify the pathogenesis of NEC. This review focuses on the currently known death modes of IECs in NEC mainly including apoptosis, necroptosis, pyroptosis, ferroptosis, and abnormal autophagy. Furthermore, we elaborate on the prospect of targeting IECs death as a treatment for NEC based on exciting animal and clinical studies.